Effects of ESG Disclosure, Return on Assets, Cash Reserves, Leverage, Firm Size, and Governance Controls on Asia-Pacific Energy Firm Value - Salsabila Suci Dwi Mawarni; Rr. Sri Saraswati (Academic Bright Collaboration, 2026)
Purpose – This research aims to examine the relationship between firm value, ESG disclosure, return on assets (ROA), cash reserves (CR), leverage (LEV), and firm size for energy businesses listed on the Asia-Pacific stock market from 2021 to 2024. In order to delve further into the impact of corporate governance in the link between these parameters and Firm Value, the research additionally accounts for variables including board size, women on board, and board independence.Methods – The method used is panel regression analysis. The data comes from energy sector companies listed in Refinitiv Eikon across various Asia-Pacific countries. The study period is from 2021 to 2024. The initial dataset of 534 observations, 248 observations met the screening criteria and were included in the final analysis.Findings – The results show that ESG Disclosure has a significant negative effect on Firm Value, and ROA, Cash Reserves, Leverage and Firm Size have a significant positive effect. This model is statistically significant at the same time. Study implications – This research offers practical implications to companies, policymakers and stakeholders. Based on agency theory, good corporate governance and financial management practices are expected to contribute to the alignment of managerial decision-making with the interests of shareholders and stakeholders, to promote sustainable behavior and improve corporate value. Originality – This study fills the empirical gap in limited Asia-Pacific evidence, addresses the theoretical gap in understanding the relationship among sustainability legitimacy, financial conditions, and oversight mechanisms, and eliminates the methodological gap, thus expanding the understanding of the multidimensional factors that determine Firm Value in the context of the energy transition.